The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/antibiotics12050926
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of blaKPC-2 and blaNDM-1 Plasmids of a K. pneumoniae ST11 Outbreak Clone

Abstract: The most common resistance mechanism to carbapenems is the production of carbapenemases. In 2021, the Pan American Health Organization warned of the emergence and increase in new carbapenemase combinations in Enterobacterales in Latin America. In this study, we characterized four Klebsiella pneumoniae isolates harboring blaKPC and blaNDM from an outbreak during the COVID-19 pandemic in a Brazilian hospital. We assessed their plasmids’ transference ability, fitness effects, and relative copy number in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Although less prevalent than the carbapenemase-coding bla KPC-2 gene, several studies demonstrated the occurrence of bla NDM-1 among clinical K. pneumoniae in Brazil, (17) including the ST11 lineage, where this gene was found in the context of an IncC plasmid. (18) Interestingly, the bla NDM-1 occurrence in Brazil was not restricted to clinical settings since it had already been found in environmental K. pneumoniae isolates recovered from both surface waters, (19) and wastewater treatment plants (WWTPs). (20) Most of the genes composing the resistome were flanked or in the vicinity of insertion sequences and plasmid-related genes, the exception was the tetD, fosA5, and bla SHV-11 , which were chromosomally encoded.…”
Section: Resultsmentioning
confidence: 99%
“…Although less prevalent than the carbapenemase-coding bla KPC-2 gene, several studies demonstrated the occurrence of bla NDM-1 among clinical K. pneumoniae in Brazil, (17) including the ST11 lineage, where this gene was found in the context of an IncC plasmid. (18) Interestingly, the bla NDM-1 occurrence in Brazil was not restricted to clinical settings since it had already been found in environmental K. pneumoniae isolates recovered from both surface waters, (19) and wastewater treatment plants (WWTPs). (20) Most of the genes composing the resistome were flanked or in the vicinity of insertion sequences and plasmid-related genes, the exception was the tetD, fosA5, and bla SHV-11 , which were chromosomally encoded.…”
Section: Resultsmentioning
confidence: 99%
“… 37 Although we could not measure the fitness cost of this plasmid, we suspected that the loss of horizontal transfer ability was a manifestation of fitness cost. Furthermore, although there have been many reports on the concurrence of the bla NDM -plasmid and bla KPC -plasmid in the same K. pneumoniae isolate, 9 , 16 , 38 the same plasmid co-harboring bla NDM and bla KPC in K. pneumoniae has not yet been reported. However, with the widespread use of ceftazidime/avibactam and frequent combined with carbapenems in clinical practice, plasmids co-carrying these two critical carbapenemase genes might gradually gain a selection advantage during continuous evolution.…”
Section: Discussionmentioning
confidence: 99%